The effect of overlying calcification on lumbar bone densitometry - Drinka, P J; DeSmet, A A; Bauwens, S F; Rogot, A (Calcified tissue international, 1992)
We studied bone mineral density (BMD) of the spine using dual photon absorptiometry, as well as standard anterior-posterior and lateral lumbar spine X-ray film in 113 ambulatory elderly male volunteers with a mean age of 72 years (range 66-91 years). Each subject had three measurements taken for lumbar vertebrae 1 through 4: BMD, length of aortic calcification (AC), and degenerative facet sclerosis graded 0-3. A separate statistical model was fit to BMD for each vertebra using analysis of covariance. AC did not contribute significantly to BMD. BMD was increased by 0.28-0.03 g/cm2 (L1-L4) with a sclerosis score of 2, and by 0.47-0.25 g/cm2 with a sclerosis score of 3, P less than 0.001. The association between increased BMD and overlying facet sclerosis may be related to the bone density within the sclerosis itself or to an association between degenerative joint disease and a generalized increase in subchondral bone.